KNOWLEDGE, PRACTICES, AND CONSTRAINTS AMONG BREASTFEEDING EMPLOYEES TOWARDS IMPLEMENTATION OF LACTATION AREA - Villarama, Joseph A.; Fabros, Bench G.; Angeles, Cristina I.; Dela Cruz, Lyan Mae Micah V.; Dela Fuente, Abegail V.; Concepcion, Emily A.; Antalan, Jorri Anne Amethyst R.; Barcelita, Karen Jean C. (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Breastfeeding empowers women and children and working mothers who revolutionize the workplace globally, specifically in carrying mutual roles as employees delivering quality service to humanity and mothers nurturing their children. This study explored the knowledge, practices, and constraints among breastfeeding working mothers in Region III, Philippines, towards implementing lactation areas. A mixed-methods approach combined a quantitative survey with a qualitative semi-structured interview component. Findings showed a high prevalence of breastfeeding among working mothers, coupled with a good level of knowledge about breastfeeding practices. However, constraints such as lack of lactation areas in offices, heavy workload, and limited support were revealed, thus foregrounding the need for institutionalized policies and guidelines to establish lactation areas in offices, promote breastfeeding, and support working mothers and their welfare, anchored on sustainable development goals (SDGs). By addressing these issues, workplaces position a more conducive environment for breastfeeding mothers, contributing to improved maternal and infant health outcomes. Further, this research provides valuable insights for policymakers, employers, and healthcare providers in initiating more effective strategies to support breastfeeding working women. Through the documented findings and by providing concrete recommendations for policy and infrastructure, this research advances the shaping of a more breastfeeding-friendly environment, promotion of maternal and infant health, supporting SDG 3-good health and well-being, and enhancement of workplace productivity towards achieving SDG 8-decent work and economic growth and SDG 5-gender equality.